Percepción de los padres o cuidadores de los niños de la encuesta de conocimientos, actitudes y prácticas en salud bucal dirigida a niños de 6 a 12 años (2021)
Describe the perception of parents or caregivers of children of the survey of knowledge, attitudes and practices in oral health called "Smiling chameleon take care of your teeth" for children 6 to 12 years.